Health Seeking Behavior and Utilization of Health Care Services in Eastern Hilly Region of Nepal - Bhattarai, Sailesh; Parajuli, Surya Bahadur; Rayamajhi, Rajan Bikram; Paudel, Ishwari Sharma; Jha, Nilambar (Journal of College of Medical Sciences-Nepal, 2015)
no Background & Objectives: Preventive, promotive, curative, and rehabilitative health care services depend not only in availability & accessibility of it but also on awareness and attitude of the people and various inter-woven social structure that determines in making choice. The objective of this study was to explore health seeking behavior and utilization of health care services in the rural places in VDCs of Ilam district of Eastern Nepal. Materials & Methods: A cross sectional study was conducted in between period of March 25th 2013 to April 10th 2013 Fikkal and Pashupatinagar VDCs in Ilam district with sample of 300 people. Data was collected using a semi-structured questionnaire. Results: One fifth of the populations were found to be seeking traditional healers’ service and 80 percent among modern treatment system were relying on private treatment facility for treating sickness. People who had lived more than 20 years in that place and who felt modern health services were costly were likely to use service of traditional healers. Similarly people suffering from chronic illness, having health facility more than 30 minutes and using stretcher or walking as means of transportation were using government health centers more compared to private services. Conclusion: Significant people still use traditional healers’ service and the government health facility utilization was low as compared to private. The people living for longer period in that place and having the concept that modern health centers are costly were primary user of traditional healing system. Health facility nearby or people who could afford for automobile travel facilities were using costly private health centers. JCMS Nepal. 2015; 11(2):8-16